2009
DOI: 10.1080/13670050802149499
|View full text |Cite
|
Sign up to set email alerts
|

Language transmission revisited: family type, linguistic environment and language attitudes

Abstract: To cite this article: Doris Schüpbach (2009) Language transmission revisited: family type, linguistic environment and language attitudes, International Journal of Bilingual Education and Bilingualism, 12:1, 15-30,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 15 publications
3
29
0
1
Order By: Relevance
“…This ideology was shared by all of the interviewees, despite significant reported variation in their family language practices, sign language abilities, and affiliations with Deaf and Hearing cultures and communities. To our knowledge, such a language ideology is not similarly pervasive among spoken-language bilingual families, although many researchers have remarked on the effort required on the part of parents who seek to transmit minority language competence to their children (e.g., Kasuya, 1998;Schüpbach 2009), as well on the regret or shame that some adults feel at not having learned their family's heritage language well enough to forestall family-internal communication barriers (e.g., Cho, Cho, & Tse, 1997;Hinton, 1999). Some researchers have also reported on the obligation felt by younger spoken-language bilinguals to switch to the family heritage language out of respect to an older monolingual family member (Hinton, 1999).…”
mentioning
confidence: 99%
“…This ideology was shared by all of the interviewees, despite significant reported variation in their family language practices, sign language abilities, and affiliations with Deaf and Hearing cultures and communities. To our knowledge, such a language ideology is not similarly pervasive among spoken-language bilingual families, although many researchers have remarked on the effort required on the part of parents who seek to transmit minority language competence to their children (e.g., Kasuya, 1998;Schüpbach 2009), as well on the regret or shame that some adults feel at not having learned their family's heritage language well enough to forestall family-internal communication barriers (e.g., Cho, Cho, & Tse, 1997;Hinton, 1999). Some researchers have also reported on the obligation felt by younger spoken-language bilinguals to switch to the family heritage language out of respect to an older monolingual family member (Hinton, 1999).…”
mentioning
confidence: 99%
“…Teachers' contradictory beliefs, as noted above, point to an inherent tension between maintaining the home language and learning a second language. In regard to this tension, many immigrant parents from a variety of nationalities, including Latino/Hispanic parents, regretfully describe that once children learn the mainstream language, they can be resistant to using the home language and often begin to lose their home language and culture (Good et al, 2010;Kim, 2011;Schüpbach, 2009;Worthy & Rodríguez-Galindo, 2006). Some parents persist in teaching their children the home language despite resistance, while others do not (Schüp-bach, 2009).…”
Section: Value Of Languagementioning
confidence: 95%
“…First, parents and teachers report that children learn a second language quickly and effortlessly (King & Fogle, 2006;Petit, 2011;Schüpbach, 2009). Petit's (2011) review of the literature indicated that teachers believe that learning a second language occurs much more quickly than evidence supports (e.g.…”
Section: Second Language Acquisitionmentioning
confidence: 97%
“…Children are socialized for L1 and L2 development in the home (Reyes 2011), and learn about expectations of socially acceptable speech through interactions with different generations of their families (Park 2008). Factors that have been found to influence transmission within the family include: family type, transmission strategies, and language attitudes and beliefs of the parents (Schüpbach 2009). Parental perceptions about the benefits of bilingualism in their children have been found to be of particular importance in this process (Reyes 2011;Velázquez 2009;King, Fogle, and Logan-Terry 2008;De Houwer 2009).…”
Section: Reported Interlocutors In Spanishmentioning
confidence: 99%